2019
DOI: 10.1194/jlr.m091173
|View full text |Cite
|
Sign up to set email alerts
|

Rosiglitazone remodels the lipid droplet and britens human visceral and subcutaneous adipocytes ex vivo

Abstract: White adipocytes are specialized cells that have a very high capacity to esterify and store FAs as triglyceride (TAG) within a single lipid droplet (LD) and release them as required by variations in nutritional state (1). In obesity, the adipocyte must cope with an increased flux of FAs from the diet and higher basal lipolysis (2, 3). If these FAs are not efficiently esterified or oxidized, unbound FAs within the cell cause lipotoxic stress with deleterious consequences for adipocyte metabolic and endocrine fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 71 publications
6
33
1
Order By: Relevance
“…MiR-27b/PPARγ pathway can regulate lipid metabolism and both ATGL and LPL are shown to accelerate TG hydrolysis to release fatty acids for oxidation ( Schoonjans et al, 1996 ; Lee et al, 2019 ). It is reported that miR-27b could inhibit LPL mRNA expression, while PPARγ regulated the mRNA expression of ATGL and LPL ( Schoonjans et al, 1996 ; Kershaw et al, 2007 ; Karbiener et al, 2009 ; Lee et al, 2019 ). Therefore, miR-27b/PPARγ pathway may affect ATGL and LPL mRNA expression, which in turn causes protein expression changes of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-27b/PPARγ pathway can regulate lipid metabolism and both ATGL and LPL are shown to accelerate TG hydrolysis to release fatty acids for oxidation ( Schoonjans et al, 1996 ; Lee et al, 2019 ). It is reported that miR-27b could inhibit LPL mRNA expression, while PPARγ regulated the mRNA expression of ATGL and LPL ( Schoonjans et al, 1996 ; Kershaw et al, 2007 ; Karbiener et al, 2009 ; Lee et al, 2019 ). Therefore, miR-27b/PPARγ pathway may affect ATGL and LPL mRNA expression, which in turn causes protein expression changes of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous reports, addressing a similar lipid droplet phenotype to represent sites of lipolysis [ 18 , 21 ]. Also, the significance of these lipid droplet compartments is supported by Lee M-J et al, which detected small lipid droplets (SLDs) in human adipocytes following Rosiglitazone-treatment [ 19 ]. In contrast to our observation, SLDs were only visible in Rosiglitazone-treated cells, whereas we find a similar phenotype independent of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only few reports have previously reported a similar lipid droplet phenotype in primary adipocytes. Lipid droplet patches were suggested to resemble sites of lipolysis [ 18 ], and small lipid droplets, decorated with mitochondria, was proposed to form following Rosiglitazone treatment [ 19 , 20 ]. Further, tiny microlipid droplets (<1 μm in diameter) were formed close to the cell surface following acute adrenergic stimulation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rosi and other thiazolidinedione (TZD) analogs have been used as insulin‐sensitizing drugs in the treatment of type 2 diabetes mellitus (T2DM) 16 . Rosi is commonly used in cell culture to promote adipogenesis as well as induce browning of white adipocytes 17‐20 . It is postulated that Rosi's browning effect is a result of its PPARγ‐agonist activity 18,21 .…”
Section: Introductionmentioning
confidence: 99%